The Effect of Some Risk Factors Participating in the Incidence of Chronic Renal Failure - abudlsttar, azzam (University of Thi-Qar Journal of Science, 2011)
The risk factors of chronic renal failure (CRF), including diabetes and hypertension, are described in present study. Also, study involved the effect of lifestyle factors of CRF, such as(age, gender, smoking, chronic disease and area of residence). Also the study included anestimation of urea and creatinine in serum blood of chronic renal failure (CRF) which treatedwith hemodialysis. The urea and creatinine were tested in the present study only for practicalpurposes because of a good standard for determining kidney functions. Blood samples of (30)patients with chronic renal failure from both sexes were compared with (50) samples takenfrom healthy individuals as a control group.The results demonstrated a significant elevation inblood urea and creatinine concentrations for patients with (CRF) in compared to controlgroup. The hemodialysis process caused a significant reduction (P<0.05) in the concentrationof urea and creatinine, the results also demonstrated that the some risk factors greatly affecton incidence of chronic renal failure.